PERMAINAN TRADISIONAL “GAPREK KEMPUNG” SEBAGAI MEDIA PEMBELAJARAN PADA MATA PELAJARAN EKONOMI KELAS VII - Fera Wulandari; Wahjoedi Wahjoedi; Sugeng Hadi Utomo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2017)
The purpose of this study is (1) to produce a media product of social science learning traditional game Gaprek Kempung by utilizing the existing facilities in the surrounding environment, (2) to determine the effectiveness of the development of instructional media of social science traditional games Gaprek Kempung to improve learning outcomes on economic subjects grade VII SMP N 1 Tumpang. Based on the analysis testing the effectiveness of instructional media traditional game Gaprek Kempung by using software IBM SPSS 24 with the formula t-test, t-hitung obtained from posttest control class and experimental class SMP N 1 Tumpang amounted to 2,763 with t-table value is 2.005 thus t-hitung> t-tabel which means an increase in the economic value of learning outcomes experimental class is better than the control class. Furthermore, gained a significance value of 0.007 <α (0.05), indicating that H1 accepted meaning experimental class is better than the control class. This study showed that media learning traditional games Gaprek Kempung further enhance the economic value of student learning outcomes compared with no use of instructional media. This means media learning traditional game Gaprek Kempung is worthy to be used to improve students’ learning outcomes and media learning traditional game Gaprek Kempung is effectively to improve students’ learning outcomes.Tujuan penelitan ini adalah (1) untuk menghasilkan sebuah produk media pembelajaran IPS permainan tradisional Gaprek Kempung dengan memanfaatkan sarana yang ada di lingkungan sekitar, (2) untuk mengetahui kefektifan pengembangan media pembelajaran IPS permainan tradisional Gaprek Kempung untuk meningkatkan hasil belajar pada mata pelajaran ekonomi siswa kelas VII SMPN 1 Tumpang. Berdasarkan hasil analisis uji keefektifan media pembelajaran permainan tradisional Gaprek Kempung dengan menggunakan software IBM SPSS 24 dengan rumus uji t-test, nilai thitung yang didapatkan dari posttest kelas kontrol dan kelas eksperimen SMPN 1 Tumpang sebesar 2,763 dengan nilai t-tabel adalah 2,005. Dengan demikian, t-hitung>t-tabel yang berarti peningkatan nilai hasil belajar ekonomi kelas eksperimen lebih baik daripada kelas kontrol. Selanjutnya, didapatkan nilai signifikansi sebesar 0,007<α (0,05) yang menunjukkan bahwa H1 diterima artinya kelas eksperimen lebih baik dari pada kelas kontrol. Penelitian ini menunjukkan bahwa media pembelajaran permainan tradisional Gaprek Kempung lebih meningkatkan nilai hasil belajar ekonomi siswa dibandingkan tanpa menggunakan media pembelajaran. Hal ini berarti media pembelajaran permainan tradisional Gaprek Kempung layak digunakan untuk meningkatkan hasil belajar siswa dan media pembelajaran permainan tradisional Gaprek Kempung efektif untuk meningkatkan hasil belajar siswa.